Fatores associados à qualidade de vida relacionada à saúde e a resiliência de pacientes oncológicos em tratamento quimioterápico e de seus familiares - Cordeiro, Larissa Martins (2018)
Cancer is considered a public health problem. Upon receiving the diagnosis of cancer, the individual may undergo changes in their habits and ways of living, which may compromise their health-related quality of life (HRQL) and their family members. The assessment of HRQoL and the resilience of oncology patients and their relatives can provide useful clinical information about the real impact on the sense of well-being and satisfaction with life and may favor the reduction of the impacts of clinical practice. The general objective was to evaluate the relationship between HRQoL and resilience and its association with self-esteem, hope, spirituality and anxious and depressive symptoms of cancer patients on chemotherapy and their relatives. This is a correlational cross-sectional study with a quantitative approach that was carried out at Instituto Amaral Carvalho. The sample consisted of 130 cancer patients on chemotherapy (QT) and 130 family members. In the individual interview, the following instruments were applied: Sociodemographic, Clinical and Health Characterization, EORTC-QLQ-C30 (this only in the (ERH), Herth Hope Scale (EEH), Pinto and Parent-Spirituality Scale (EEPPR), Rosenberg Self Esteem Scale (EAR) and Hospital Anxiety Depression Scale (HADS) . The analysis was performed by descriptive statistics, correlation analysis, mean and univariate and multivariate logistic regression. The project was approved by the Research Ethics Committee (CEP) of the Federal University of São Carlos (Opinion No. 1,680,639) and the Amaral Carvalho Hospital (Opinion No. 1,842,423). The results showed that patients presented a better perception of HRQoL in the "mental health" dimension of the SF-36 (70,98) and in the "social function" of EORTC-QLQ-C30. The worst perception of HRQOL was attributed to the "physical aspects" of the SF-36 (27,88) and the "fatigue" symptom of the EORTC-QLQ-C30 (29,15). Already the relatives indicated a better perception of HRQOL in "functional capacity" (86,69) and worse perception in "vitality" (66,04), both domains of the SF-36. A high level of resilience was observed between the patients (n = 63; 48.46%) and the relatives (n = 72; 55.38%). There was a relationship between HRQoL and the resilience of the interviewees, including patients and relatives with a high level of resilience presented better HRQoL. Patients and families with better HRQL and high level of resilience presented higher levels of spirituality, hope and self-esteem, and lower levels of anxious and depressive symptoms. Among the factors associated with the best HRQoL in patients with QT cancer, the lowest age, lower educational level, no use of medication, presence or absence of metastasis, no pain, high resilience, spirituality, hope and self-esteem, in addition to the low level of anxious and depressive symptoms. As for the relatives, the factors were male gender, not to help the family income, not to live with the patient, a high level of self-esteem and a low level of anxious and depressive symptoms. Among the factors associated with the high resilience of cancer patients in QT were the high level of hope and spirituality and the low level of depressive symptoms. For family members he found himself to be a practitioner of a religion and a high level of hope. It was concluded that there is a relationship between HRQoL and the resilience of cancer patients in QT and their relatives.